Pengaruh Profesionalisme Sumber Daya Manusia terhadap Kinerja Karyawan di Kantor Samsat Wilayah II Kota Palembang - Ambiko, Diajeng Woro; Hadjri, M. Ichsan; Santati, Parama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of human resource professionalism on employee performance in the SAMSAT office regional II, Palembang City. The population in this study is all employees of the SAMSAT office regional II, Palembang City which amounts 72 employees. This study used saturated sampling technique. Data used in this study is primary data that collected by quisioner technique. The data analysis technique used is simple linear regression analysis. Based on the result of the study showed that the human resource professionalism had a positive and significant effect on employee performance of the SAMSAT office regional II, Palembang City. Keywords: Human Resource Professionalism, Employee Performance